Analisis Faktor Yang Berhubungan Dengan Mutu Pelayanan Kesehatan Terhadap Kepuasan Pasien Rawat Inap Di RSUP. Dr. Wahidin Sudirohusodo Makassar 2020 - Ulfa Mutmainnah; Reza Aril Ahri; Arman (Journal of Muslim Community Health, 2021)
Background: Quality of service at the hospital is an important factor in creating patient satisfaction. This study aims to determine the relationship between the quality of health services based on the dimensions of technical competence, effectiveness, comfort, safety, human relations, continuity and timeliness of service to patient satisfaction of Wahidin Sudirohusodo Hospital. Methods: This type of research is a quantitative study using a cross sectional study design. The population in this study were 25,257 respondents. Sampling using proportional sampling, obtained a sample of 123 respondents. Data analysis used univariate and bivariate and multivariate analysis with the chi square test. Results: Based on the results of the study, the variables related to the quality of health services on patient satisfaction of Wahidin Sudirohusodo Hospital Makassar City were effectiveness (p = 0.000), comfort (p = 0.002), safety (p = 0.000), human relations (p = 0.000). ), flexibility (p = 0.006), and timeliness (p = 0.000). Meanwhile, the variable that was not related to the quality of health services on patient satisfaction was technical competence (p = 0.607). And for the variable that most influences patient satisfaction is the relationship between humans with the exp (B) value of 13.058. Conclusion: There is a relationship between service quality (effectiveness, comfort, safety, human relations, flexibility and timeliness) on patient satisfaction of Wahidin Sudirohusodo Hospital, Makassar City.